"Made This Way for a Reason": Body Satisfaction and Spirituality. Issue 1 (8th April 2013) - Buser, Juleen K.; Parkins, Rachael A.
<x xml:space="preserve">Abstract</x> Nine female participants shared their experiences of body satisfaction, spiritual beliefs, and the intersection of these domains. Using phenomenological inquiry, the authors identified 6 themes in participant interviews. The authors discuss ways in which this study extends previous research, in addition to providing suggestions for counseling practice.